TEMPAT-TEMPAT SAKRAL DAN PENERAPAN SAWORA DALAM MASYARAKAT KAMPUNG ISENEBUAI DI KAWASAN TAMAN TELUK CENDERAWASIH - Irman Rumengan (Fakultas Ilmu Budaya Universitas Diponegoro, 2017)
Cultural heritage is an important value owned by some communities in the area of Teluk Cenderawasi National Park. One of which is the legacy of important places owned by Isenebuai village community. Isenebuai village community has Sawora or